Working mechanism evaluations and simplified models of corner bracket type inter‐module connections. (13th April 2021) - Zhao, Fengtao; Yu, Yujie; Lin, Siwen; Man, Mengke; Ding, Faxing
Summary: In modular steel buildings, the corner bracket type inter‐module connection is a commonly used way of connecting adjacent modules together. However, the detailed working mechanisms of this connection are still not well known. In this study, the mechanical properties of two corner bracket type inter‐module connections were identified based on reported tests and refined finite element simulations. A simplified multi‐spring model of the corner bracket type inter‐module connections was proposed and was then incorporated into the two‐dimensional analysis of a framed modular building and a braced modular building to investigate the effect of connection properties on lateral sway performance of modular structures. Results indicated that the corner bracket type inter‐module connection had a lower tensile stiffness and resistance than compressive ones. Tensile and bending resistances of the connection were correlated with each other and were determined by the out‐of‐plane prying deformation of bracket endplates. The inter‐module connection possessed the extrusion‐resisting and separation‐permitting behavior between assembled brackets. The lateral sway performance of the pure framed modular building was closely related to the vertical shear stiffness of inter‐module connections. However, in the braced modular building, the tension and horizontal shear stiffnesses of inter‐module connections were the critical aspects.